Isolation and identification of Riemerella anatipestifer from ducks in Malaysia - How, Yan Xing; Bejo, Siti Khairani; Zakaria, Zunita (2011)
Riemerella anatipestifer is the primary etiological agent of contagious septicemic diseases among ducks. The study is the first atempt to isolate and identify R. anatipestifer from ducks in Malaysia. In this study, ten diseases Khaki-Campbell ducks and forty healthy Khaki-Campbell ducks were selected. A pharyngeal swab was collected from each selected ducks. One strain of R. anatipestifer was successfully isolated out of the ten diseased ducks and identified using conventional biochemical tests. R. anatipestiferwas isolated from the healthy ducks. The R. anatipestifer isolate was then subjected to antibiotic sensitivity testing using Kirby-Bauer method. The sensitivity of R. anatipestifer to penicillin G. enrofloxacin, oxytetracycline, gentamicin, neomycin, and ceftiofur was determined. R. anatipestifer was found to be highly sensitive to enrofloxacin, oxytetracycline and neomycin, intermediately sensitive to gentamicin and resistant to penicillin G and ceftiofur.